A new species of the genus Phymorhynchus (Neogastropoda: Raphitomidae) from a hydrothermal vent in the Manus Back-Arc Basin - Zhang, Shuqian; Zhang, Suping (Zootaxa, 2017)
During an investigation carried out by the Institute of Oceanology, Chinese Academy of Sciences (IOCAS), three living raphitomid specimens were collected from a hydrothermal vent site in the Manus Back-Arc Basin. Observations of the shell, external anatomy and radular morphology reveal that they represent an undescribed species of the genus Phymorhynchus Dall, 1908. In this paper, we describe and illustrate this species as Phymorhynchus oculatus sp. nov. The new species is most similar in general shell shape to Phymorhynchus buccinoides Okutani, Fujikura & Sasaki, 1993, but can be distinguished from it by having spiral cords over the whole shell surface and much longer marginal tooth with a distal barb. A list of species of Phymorhynchus from vent/seep habitats is also given.